2006
DOI: 10.1353/sgo.2006.0033
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Heat Island and Local Temperature Variations in Orlando, Florida

Abstract: Cities artificially alter local climates affecting economic and biological processes. This study examined air temperatures in Orlando's urban canopy layer using a network of twenty-nine fixed-point stations from September ∞ΩΩΩ to December ≤≠≠∞. Urban Heat Island (UHI) statistics were calculated using two stations that were representative of an urban and rural setting. Orlando's UHI develops best on calm, clear nights during dry months: its maximum magnitude exceeds ∫\C. Orlando's UHI, however, is predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Various potential causes for this decrease in DTR include greenhouse warming and associated changes, increases in atmospheric aerosol concentrations, contrails, increased cloud cover at low levels, increases in precipitation, irrigation and soil moisture, stable nighttime boundary layer dynamics, the urban heat island effect, or a combination of these factors. Yow and Carbone () found that the urban heat island in Orlando, Florida, is more marked (up to 8 °C) on calm clear nights when there is less vertical and horizontal mixing and the potential for greater rural cooling rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various potential causes for this decrease in DTR include greenhouse warming and associated changes, increases in atmospheric aerosol concentrations, contrails, increased cloud cover at low levels, increases in precipitation, irrigation and soil moisture, stable nighttime boundary layer dynamics, the urban heat island effect, or a combination of these factors. Yow and Carbone () found that the urban heat island in Orlando, Florida, is more marked (up to 8 °C) on calm clear nights when there is less vertical and horizontal mixing and the potential for greater rural cooling rates.…”
Section: Resultsmentioning
confidence: 99%
“…Kukla and Karl () found that globally since the 1950s, daily minimum temperatures have risen three times as fast as daily maximum temperatures, resulting in a net decrease of the daily temperature range (DTR). Yow and Carbone () found that the ‘urban heat island’ in Orlando, Florida, is more marked (up to 8 °C) on calm clear nights when there is less vertical and horizontal mixing and the potential for greater rural cooling rates.…”
Section: Florida Climatic Influences and Previous Studiesmentioning
confidence: 99%
“…2006; Miyazaki et al. 2006; Runnalls and Oke 2000; Yow and Carbone 2006), mobile traverses (e.g. Bottyán et al.…”
Section: Defining and Observing The Urban Heat Islandmentioning
confidence: 99%
“…Examining air temperatures in the urban canopy layer usually entails using fixed-point stations (e.g. Fortuniak et al 2006;Ji et al 2006;Miyazaki et al 2006;Runnalls and Oke 2000;Yow and Carbone 2006), mobile traverses (e.g. Bottyán et al 2005;Wong and Yu 2005), or a combination of both (e.g.…”
Section: ∆T = T Urban -T Ruralmentioning
confidence: 99%
“…The urban climate have been studied in numerous cities around the world because the myriad factors leading to the existence of an urban heat island differ from city to city (Yow & Carbone, 2006). The temperature conditions varied between different landscapes communities within urban area (Cui, Liu, Kuang, & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%